Presentation - Ocampo Flórez, Esteban; Pontificia Universidad Javeriana (Editorial Pontificia Universidad Javeriana, 2012)
All year long and almost every year, those who are lucky to be near institutions whose mission is associated with the production, discussion and circulation of knowledge, are overwhelmed by the amount of activities in which research progress, intervention products and reflection results of an important group of academics, researchers and professionals in general, are showed.